Translation and Validation of the Digital Stress Scale (DSS) in Indonesian Version - Rizal Kurniawan; Elrisva Magistarina; Rahayu Hardianti Utami; Puspaneli; Dedi Supendra (Psympathic : Jurnal Ilmiah Psikologi, 2026)
This study aimed to translate the digital stress scale (DSS) into Indonesian version using three stages. Study 1 translated and validated the DSS into Indonesian using a back-translation approach with six experts and produced a scale translation script in the Indonesian version. Subsequently, study 2 validated the DSS in the Indonesian version through exploratory factor analysis (EFA), and a total of 453 respondents participated in this stage. EFA results showed a KMO value of .87, accounting for 56.3% of the total variance. The analysis identified five factors, consistent with the original version, but two items were excluded because of low factor loading. Study 3 was conducted to confirm the model from Study 2 using confirmatory factor analysis (CFA), and a total of 544 respondents participated. CFA showed that the DSS has five dimensions, similar to the original version, with a CFI value = .93, TLI = .91, NFI = .90, GFI = .91, and RMSEA = .07. However, the results did not support measurement invariance across gender. In conclusion, this study produced an instrument with good psychometric properties for measuring stress resulting from digital activities.